Environmental and social transport costs: a case study of Ireland - O'MAHONY, MARGARET MARY (Transportation Research Board of the National Academies, 2005)
The aim of the EU funded UNITE research project was to provide information about the costs, benefits and revenues of all transport modes including environmental and social costs. The project involved compiling accounts for 18 countries across Europe with each country having its own set of accounts in such a format that comparisons, where possible, could be made. The paper focuses on the latter two sets of costs i.e. environmental and social for Ireland. The account presented here is a pilot account (rather than an ideal account) i.e. the actual, feasible accounts given the available data. The costs are reported and documented at the current level of transport demand for the reference year 1998 but data for 1996 and projections for 2005 are also included where data and historical trends allow. The paper concludes with some comparisons between transport costs in Ireland and some of the other European countries examined in the UNITE project. The accident costs in Ireland (?50/capita) lower than those for Denmark (?120/capita), Netherlands (?80/capita) and about the same as Spain (?50/capita), are considerably less than those in Austria (?160/capita) and larger than those of France (?20/capita) and the UK (?25). Noise costs are ?100/capita and are close to those of France, Spain and the UK. They are higher than those of Netherlands (?20/capita) and Austria (?40/capita).
Annual Meeting of the Transportation Research Board: 84th: Washington, D.C.: 2005
PUBLISHED
Keywords: transport systems - Europe; transport network - Europe; UNITE Project